Specific Exercise, but Not Training Program, Affects Regional Hypertrophy: A Case Study of Preacher Curl - Ratanyoo Longrak (European Journal of Human Movement)
This study explored the regional muscle hypertrophic effect of the preacher curl training between two distinct program designs. Twenty healthy young males (age: 21.1±0.4 years; height: 174.1±5.1 cm, weight: 69.1±11.3kg) were recruited and randomly allocated to the 6-week programs of either mechanical tension program (MT) or mechanical tension with metabolic stress program (MTMS). Biceps brachii cross-sectional area (CSA) and thickness at proximal and distal regions were assessed by magnetic resonance imaging (MRI) and B-mode ultrasonography (US), respectively. Furthermore, fascia thickness was measured together with muscle thickness. Results indicated significant increases in biceps brachii CSA at both the proximal and distal regions in both programs (p < 0.05). Interestingly, muscle CSA at the distal region exhibited a more pronounced growth with larger effect sizes compared to the proximal region in both MT (∆12.15%, p = 0.000, ES = Moderate vs ∆8.26%, p = 0.038, ES = Small) and MTMS (∆16.92%, p = 0.008, ES = Moderate vs ∆9.02%, p = 0.005, ES = Small). Moreover, US further confirmed these findings, both MT and MTMS showed only significant increases in biceps brachii thickness at the distal region (∆25.95%, p = 0.000, ES = Large, and ∆21.76%, p = 0.009, ES = Large, respectively). Interestingly, fascia remodeling interestingly showed that significant thickness increased at distal region only in MTMS (∆47.27%, p = 0.006, ES = Large). In conclusion, our study confirmed that the preacher curl exercise per se induced regional hypertrophy preferentially in the distal region of the biceps brachii muscle, while resistance training program design had no discernible effect on this hypertrophic pattern.